Kandungan senyawa capsaicin dalam cabai (Capsicum Annuum L) sebagai anti hama pada sayuran: Kajian pustaka - Risma Khoerunisa; Risya Jheniar Nur Siti Khamilah; Dzuhrika Gantari Ayuanindya; Hertien Koosbandiah Surtikanti; Didik Priyandoko (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Vegetables are one of the most widely cultivated crops because of their important role in fulfilling food nutrition. In the implementation of vegetable cultivation, there will be obstacles such as pest and disease attacks. Chili plants can be used as vegetable pesticides because they have capsaicin compounds that can have a negative effect on pests. This literature review aims to discuss capsaicin compounds as anti-pests in vegetables, namely by causing the death of vegetable pests in several studies. The method used was a literature study. The results in the four articles reviewed show that the capsaicin compound in chili peppers can be used as a vegetable pesticide because it can affect digestion, inhibit growth and nerve work in pests which ultimately causes the death of these pests. The higher the concentration of chili extract, the higher the percentage of pest mortality. This vegetable pesticide from red chili extract can be used as an alternative to chemical pesticides.